Locus Terikat dalam Tarekat: Eksistensi Kampung Khalwatiyah Patte’ne di Tengah Urbanitas (Universitas Islam Negeri Sunan Ampel Surabaya, 2018)
An early Tasawwuf has already existed since Islam religion was first brought to Indonesia in which Tariqa traditions contributed to the spread of the faith. The Tariqa of Khalwatiyah Samman is one of the Islamic mysticisms which has developed and been in existence until now. The number of the Tariqa’s followers reaches hundred thousand of people spread in various loci including Patte’ne village in Maros Regency, South Sulawesi. The strategic location becomes an urbanity anomaly toward the surrounding integrated area. The Patte’ne village promotes its existential identity as a consistent locus tied to Khalwatiyah Tariqa. The implementation of this can be seen in the spatial pattern of the area, in the cultural values reflecting the activities applied either in daily rituals or annually ceremonial agendas, and in the human resources acted as role models adopted from the Khalwatiyah teaching. The approach of this research uses both descriptive research and a historical approach. The methods of data collecting are surveys, visual materials, and observations. The result of this research indicates that a village will stand valuable if the concept of urbanity remains existent, in the form of both social and economic systems. The implication of those various sectors can create a condition and a balancing role for all the components creating the surrounding area. It demonstrates that the existence of Patte’ne village has become a locus which energizes an urbanity performance, which means that all the available resources have respectively participated so that it creates a mutually symbiotic relationship.